Cognitive devices to communicate the economic crisis - María Enriqueta Cortés de los Ríos (Ibérica, 2010)
This paper explores how the economic crisis is reported by analysing one of the most common conceptual mappings related to the economy: ECONOMY IS A NATURAL PHENOMENON. More specifically, I analyse the use of natural disasters, weather and apocalyptic metaphors in press covers together with other elements such as metonymies, image schemas, colour and cultural aspects. The aim of this paper is to investigate how all these devices are exploited by journalists to reflect the economic crisis and to influence their readers. A cognitive-axiological approach has been used to analyse seven covers which are closely related to the above metaphors out of 51 published in 2008 in The Economist, the prestigious business and current affairs magazine. The analysis is structured according to the theory of cognitive linguistics outlined over the last three decades (amongst others see Johnson, 1987; Lakoff, 1987 & 1993; Lakoff & Johnson, 1980; Forceville, 1996 & 2006; Ruiz de Mendoza, 2000; Ungerer, 2000; Ruiz de Mendoza & Mairal Usón, 2007), but with some additional findings from other axiological contributions (Krzeszowski, 1993, 1997 & 2004; and Felices Lago, 2006 & 2008).